2021
DOI: 10.1007/s10620-021-07120-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fibrosis-4 Index Prior to COVID-19 on Outcomes in Patients at Risk of Non-alcoholic Fatty Liver Disease

Abstract: Background Severity of disease and outcomes in patient with COVID-19 has been associated with several risk factors tied to the metabolic syndrome. Aims We conducted a study with the objective of describing the association between the baseline Fibrosis-4 (FIB-4) index prior to SARS-CoV-2 infection and the severity of COVID-19 among patients at risk of non-alcoholic fatty liver disease (NAFLD). Methods This was a retrospective cohort study of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…We excluded 421 duplicated records and 285 articles, which were not relevant to the study objective after reviewing the title and abstract. Sixteen articles [ 15 , 16 , 18 , 19 , 29 40 ] were finally included after excluding 15 reports for the following reasons: (1) reports that did not report the relevant clinical outcomes or target population ( N = 8), (2) elucidations that were case reports or consisted only of comments ( N = 5), and (3) studies that reported results with an unadjusted estimate effect ( N = 2). The detailed exclusion criteria for each study are described in Supplementary Table S3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded 421 duplicated records and 285 articles, which were not relevant to the study objective after reviewing the title and abstract. Sixteen articles [ 15 , 16 , 18 , 19 , 29 40 ] were finally included after excluding 15 reports for the following reasons: (1) reports that did not report the relevant clinical outcomes or target population ( N = 8), (2) elucidations that were case reports or consisted only of comments ( N = 5), and (3) studies that reported results with an unadjusted estimate effect ( N = 2). The detailed exclusion criteria for each study are described in Supplementary Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were from Europe, and six publications were from Asia. Ten [ 15 , 16 , 18 , 29 , 31 34 , 36 , 38 ] articles reported FIB-4, three [ 30 , 35 , 40 ] reported aspartate aminotransferase (AST)/alanine aminotransferase (ALT) ratio, one [ 39 ] reported NFS, one reported FIB-4 and NFS [ 37 ], and one [ 19 ] assessed FIB-4 and Forns index score. All studies were found to be acceptable ( N ≥ 6) elucidations assessed by the NOS (see Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the prognosis of MALFD patients is determined by the severity of liver fibrosis, not by the presence of steatosis or steatohepatitis, even after the patient is infected with SARS-CoV-2 [84] , [85] . In NAFLD patients with COVID-19, an increase in the Fibrosis-4 (FIB-4) index preinfection was associated with worse clinical outcomes, and age was the strongest predictor of hospitalization and mortality [86] . Compared to patients without or with a low FIB-4 score, MAFLD patients with intermediate or high FIB-4 scores are more likely to be obese, elderly, have diabetes and have higher CRP levels, liver enzyme levels, and NAFLD fibrosis scores and lower platelet and lymphocyte counts, triglyceride levels and high-density lipoprotein cholesterol levels [87] .…”
Section: Chronic Liver Disease Complicated By Sars-cov-2 Infectionmentioning
confidence: 99%
“…To the best of our knowledge, only few studies had proposed liver brosis non-invasive scores, assessed prior to acute COVID-19 illness, to the risk of more severe disease [15], increased odds of hospitalization [23], and orotracheal intubation [19].…”
Section: Discussionmentioning
confidence: 99%